2017
DOI: 10.1016/j.vaccine.2017.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Polio immunity and the impact of mass immunization campaigns in the Democratic Republic of the Congo

Abstract: BackgroundIn order to prevent outbreaks from wild and vaccine-derived poliovirus, maintenance of population immunity in non-endemic countries is critical.MethodsWe estimated population seroprevalence using dried blood spots collected from 4893 children 6–59 months olds in the 2013–2014 Demographic and Health Survey in the Democratic Republic of the Congo (DRC).ResultsPopulation immunity was 81%, 90%, and 70% for poliovirus types 1, 2, and 3, respectively. Among 6–59-month-old children, 78% reported at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 19 publications
(17 reference statements)
3
24
0
Order By: Relevance
“…Similar campaign was conducted for polio and diphtheria. [37][38][39] Our study revealed that majority (87%) of the mothers believe in government-sponsored immunization campaign, as it is easy for them to follow-up vaccination process (p < .05). Previous studies have suggested the such vaccination campaign increases vaccination rate of the country.…”
Section: Knowledge Of Mothers On Childhood Vaccinationmentioning
confidence: 73%
“…Similar campaign was conducted for polio and diphtheria. [37][38][39] Our study revealed that majority (87%) of the mothers believe in government-sponsored immunization campaign, as it is easy for them to follow-up vaccination process (p < .05). Previous studies have suggested the such vaccination campaign increases vaccination rate of the country.…”
Section: Knowledge Of Mothers On Childhood Vaccinationmentioning
confidence: 73%
“…During the study period, trivalent OPV (types 1, 2 and 3) were used for routine vaccination while bivalent and monovalent formulations were specifically used in response to prevalent strains of circulating PVs [44]. We found a low rate of PV strains among healthy children in the Kasai Oriental and Maniema provinces of DR Congo in 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that bOPV delivered in campaigns may have lower immunogenicity in certain settings, and this finding will need to be confirmed with new field studies with bOPV. Studies with tOPV have shown conflicting results: Some serosurveys found higher type-specific seroprevalence with tOPV delivered exclusively during campaigns than the same number of doses administered through routine immunization [22], whereas other surveys found lower immunogenicity for doses delivered through campaigns in certain populations [23,24]. Factors known to interfere with the response to tOPV and bOPV, such as diarrhea and malnutrition [25][26][27], were prevalent in our population [1,12] and may have been partially responsible for the apparent lower effectiveness of bOPV observed.…”
Section: Plos Medicinementioning
confidence: 99%
“…Factors known to interfere with the response to tOPV and bOPV, such as diarrhea and malnutrition [25][26][27], were prevalent in our population [1,12] and may have been partially responsible for the apparent lower effectiveness of bOPV observed. Unfortunately, because of our limitations in accurately calculating the type and number of OPV doses received by each child and the small sample size of subgroups, we were unable to assess the per-dose immunogenicity of bOPV or the potential effects of factors such as malnutrition on seroprevalence [23,27]. The general low reliability of polio vaccination histories to estimate population immunity has also become more relevant with the intensification of immunization campaigns in areas considered at high risk for polio outbreaks, and with the use of different serotype presentations of polio vaccines [28][29][30][31].…”
Section: Plos Medicinementioning
confidence: 99%
See 1 more Smart Citation